Attention span : a groundbreaking way to restore balance, happiness and productivity - Mark, Gloria (Hanover Square Press, 2023)
"We spend an average of just 47 seconds on any screen before shifting our attention. It takes 25 minutes to bring our attention back to a task after an interruption. And we interrupt ourselves more than we're interrupted by others. In Attention Span, psychologist Gloria Mark reveals these and more surprising results from her decades of research into how technology affects our attention. She shows how much of what we think we know is wrong, including insights such as: why multitasking hurts rather than helps productivity; how social media and modern entertainment amplify our short attention spans; what drains our mental resources and how to refuel them; the four types of attention that we experience every day and how to recognize them"--